Effects of dietary inulin supplementation on the composition and dynamics of cecal microbiota and growth-related parameters in broiler chickens. (19th August 2019) - Xia, Yun; Kong, James; Zhang, Guobing; Zhang, Xuxiang; Seviour, Robert; Kong, Yunhong
ABSTRACT: Inulin, a prebiotic, is an attractive alternative to antibiotic growth promoters in chickens. Dietary supplementation with inulin can improve growth performance, carcass yield, immune system activity, and serum biochemical parameters in chickens. A few studies investigated the impact of dietary inulin supplementation on chicken intestinal microbiota. In this study, we investigated how and why dietary supplementation with 1, 2, and 4% inulin can affect body weight gain, feed intake, food conversion rate, immunological parameters, serum biochemical parameters, and composition and dynamics of the cecal microbiota of Tegel broiler chickens using quantitative fluorescence in situ hybridization (qFISH). We showed that inulin inclusion has a negative effect on growth performance parameters before day 21 and a positive effect subsequently up to day 42. Quantitative FISH data revealed an age-dependent change in the cecal microbiota in the control broilers fed no inulin. Thus, relative abundances of Firmicutes and Actinobacteria decreased from 52.8 to 48.3% of total cells and from 8.7 to 1.4% at days 7 and 42, respectively. However, relative abundances of Bacteroidetes and Proteobacteria gradually increased from 9.3 to 26.9% of the total cells and from 10.7 to 21.1%, respectively, over the same periods. Inulin inclusion appeared to lower the relative abundances of Lactobacillus johnsonii and Bifidobacterium species at an early bird age, but it subsequently significantly ( P < 0.05) increased their relative abundances. Such increases positively correlated with body weight gain of the birds, determined after day 21. Thus, dietary supplementation with inulin together with the addition of L. johnsonii and Bifidobacterium ( B. gallinarum and B. pullorum ) cultures at an early age may help overcome its early negative influence on growth performance. We believe that these findings can improve our knowledge on how inulin can change the intestinal microbiota of broiler chickens and help in developing an inulin feeding regime to optimize its beneficial role in chicken development.